Pengembangan Instrumen Telaah RPP Dan Supervisi Akademik Berbasis Keterampilan Abad 21 Guru Sekolah Binaan SPMI Kota Palangka Raya - I Wayan Sarman (Jurnal Ilmiah Kanderang Tingang, 2020)
Arranging lesson plans refers to the characteristics of students not in accordance with the demands of 21st century learning. This study aims to develop the Lesson Plan review instrument and supervision of 21st century skill-based learning using research and development (R&D). There are three design models for instrument development, namely: 1) a preliminary study, 2) the development stage, and 3) the evaluation stage. The results showed that (1) the factual model of the Lesson Plan review instrument and the supervision of learning in Central Kalimantan Province did not meet the suitability of the preliminary, core, and closing activities as well as the description in the Lesson Plan, so that it had not been used as a teacher's reference in perfecting the Lesson Plan; (2) instrument development begins with, (a) reviewing the literature so that 5 (five) components of the Lesson Plan are obtained and three stages of supervision are carried out, (b) validating the instruments according to the expert includes validity, level of importance, and usefulness on average. the average percentage reached 92.19. The evaluation phase is to test the practicality of the instrument showing (a) the observer makes it easy to study lesson plans and supervision of learning, (b) assist teachers in perfecting lesson plans according to the minimum substance in the lesson plans, (c) schools have measurement tools for lesson plans and learning supervision, and (d) Excel-based instruments that have been successfully developed refer to the skills of 21st century teachers and the industrial revolution 4.0.